MUSIK BERMANFAAT UNTUK NADI BBLR SELAMA KANGAROO MOTHER CARE - Wiwi Kustio Priliana (Universitas Jenderal Achmad Yani Yogyakarta, 2013)
Background: Kangaroo Mother Care (KMC) is a means or method of caring for LBW, where there is direct skin contact between mother and baby makes automatic adjustments to the mother's body temperature to protect her baby. Some interventions such as massage treatments in the NICU babies, Kangaroo Mother Care and listening to music has benefits baby's growth and readiness to go home and reduce maternal anxiety. Objectives: Given the benefits of music on maternal anxiety and response Kangaroo Mother Care for low birth weight. Methods: Quasi-experimental study design with Pretest and posttest Non Equivalent Control Group Design. Population: the mother and low birth weight who implement KMC. This study sampled 40 mothers and her babies. Purposive sampling with sampling, a research site in Ward General Hospital NICU Wates and RS Jogja. Independent variabel : music, the dependent variable: heart rate LBW and external variables: gestational age. The music used was Lullaby music which was captured from the internet. Analysis Data include: univariabel, bivariabel, and multivariable. Statistical tests using the Paired t-test, Independent t-test and Linear Regression with a significance level of p <0.05 and confidence interval (CI) 95%. Results: After treatment decreased heart rate of LBW 3,8 x/minute, p = 0.004. Gestational age the results were not significant (p> 0.05). Conclusion: Music has an influence on the reduction lower heart rate on the Kangaroo Mother Care for low birth weight. Keywords: Kangaroo Mother Care, LBW, Music.